Re-introducing non-optimal synonymous codons into codon-optimized constructs enhances soluble recovery of recombinant proteins from Escherichia coli - Konczal, Jennifer (PLoS One, 2019)
Gene synthesis services have largely superseded traditional PCR methods for the generation of cDNAs destined for bacterial expression vectors. This, in turn, has increased the application of codon-optimized cDNAs where codons rarely used by Escherchia coli are replaced with common synonymous codons to accelerate translation of the target. A markedly accelerated rate of expression often results in a significant uplift in the levels of target protein but a substantial proportion of the enhanced yield can partition to the insoluble fraction rendering a significant portion of the gains unavailable for native purification. We have assessed several expression attenuation strategies for their utility in the manipulation of the soluble fraction towards higher levels of soluble target recovery from codon optimized systems. Using a set of human small GTPases as a case study, we compare the degeneration of the T7 promoter sequence, the use of alternative translational start codons and the manipulation of synonymous codon usage. Degeneration of both the T7 promoter and the translational start codon merely depressed overall expression and did not increase the percentage of product recovered in native purification of the soluble fraction. However, the selective introduction of rare non-optimal codons back into the codon-optimized sequence resulted in significantly elevated recovery of soluble targets. We propose that slowing the rate of extension during translation using a small number of rare codons allows more time for the co-translational folding of the nascent polypeptide. This increases the proportion of the target recovered in the soluble fraction by immobilized metal affinity chromatography (IMAC). Thus, a “de-optimization” of codon-optimized cDNAs, to attenuate or pause the translation process, may prove a useful strategy for improved recombinant protein production.